2012
DOI: 10.1103/physrevlett.108.056602
|View full text |Cite
|
Sign up to set email alerts
|

Optically Engineering the Topological Properties of a Spin Hall Insulator

Abstract: Time-periodic perturbations can be used to engineer topological properties of matter by altering the Floquet band structure. This is demonstrated for the helical edge state of a spin Hall insulator in the presence of monochromatic circularly polarized light. The inherent spin structure of the edge state is influenced by the Zeeman coupling and not by the orbital effect. The photocurrent (and the magnetization along the edge) develops a finite, helicity-dependent expectation value and turns from dissipationless… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
185
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 197 publications
(193 citation statements)
references
References 43 publications
6
185
2
Order By: Relevance
“…In particular, this quantization still survives for elliptic polarization, upon addition of an inversion symmetry breaking term and/or in presence of orbital effects, see supplementary material of Ref. [31]. Finally, this quantization is fairly general in the adiabatic limit where it can be deduced [46] from the GoldstoneWilczek formula [47].…”
Section: Topological Invariant and Photocurrentmentioning
confidence: 91%
See 3 more Smart Citations
“…In particular, this quantization still survives for elliptic polarization, upon addition of an inversion symmetry breaking term and/or in presence of orbital effects, see supplementary material of Ref. [31]. Finally, this quantization is fairly general in the adiabatic limit where it can be deduced [46] from the GoldstoneWilczek formula [47].…”
Section: Topological Invariant and Photocurrentmentioning
confidence: 91%
“…Besides, it is natural to use photons to probe topological phases and their edge/surface states. We have studied a QSH state and its one-dimensional helical edge state in a circularly polarized radiation field [31]. Using Floquet theory, we have demonstrated that the photocurrent and the magnetization are ruled by the very same unit vector, whose winding number determines a topological invariant for the system.…”
Section: Probing Helical Edge States By Lightmentioning
confidence: 99%
See 2 more Smart Citations
“…The Floquet spectrum of a periodically driven system was shown to exhibit a variety of topological phases 7 . For instance, graphene is expected to exhibit a quantum Hall effect when subjected to radiation 9,12,13 ; a spin-orbit coupled semiconductor heterostructure (such as HgTe/CdTe wells), can be turned topological using microwave-teraHertz radiation 10 , and vice versa 14,15 .…”
Section: Introductionmentioning
confidence: 99%